(untitled) (Indian Journal of Animal Production and Management, 2023)
Marwari goats are mainly distributed in seven districts of arid western Rajasthan. This goat is a medium sized and uniformly black coloured animal with shiny light-gray skin. Horns are corkscrew type and animals have a curly tuft of hair on forehead. The data on body weight and milk yield pertaining to 133 goats were analysed. The average body weights at birth, 3, 6, 9, 12, 15, 18, 21 and 24 months age were observed to be 2.24, 8.79, 13.02, 15.76, 18.50, 22.0, 25.1, 26.0 and 28.20 kg respectively. Male animals attained higher body weights than females and twin born animals gained lower body weight than single born till one year of age; thereafter the body weight was more or less similar in both single and twin born kids. On an average 23.3 percent twinning was observed in Marwari goats. Marwari goats kidded first time at the average age of 25.5 months and most of the goats (64%) kidded in between age group of 18 to 27 months. Female born with twin birth matured faster and kidded at about 2 years of age. The body weight at first kidding of Marwari goats was more or less similar in both the categories. Twenty one percent Marwari goats were observed to be elite in the institute’s flock. Elite goats yielded 47% more milk (in 150-d lactation yield) over flock average. Goats with twin birth had significantly (P<0.05) lower milk yield both in pre-weaning and in total lactation period than single born goats. Single born goats yielded 168.9 lit and twin born goats yielded 149.7 litres of milk in total lactation length. However, the lactation length was more or less similar.